2008
DOI: 10.2139/ssrn.1318329
|View full text |Cite
|
Sign up to set email alerts
|

Computational Complexity in Additive Hedonic Games

Abstract: We investigate the computational complexity of several decision problems in hedonic coalition formation games and demonstrate that attaining stability in such games remains NP-hard even when they are additive. Precisely, we prove that when either core stability or strict core stability is under consideration, the existence problem of a stable coalition structure is NP-hard in the strong sense. Furthermore, the corresponding decision problems with respect to the existence of a Nash stable coalition structure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 62 publications
1
40
0
1
Order By: Relevance
“…This fact does not imply that checking the existence of a core stable partition is NP-hard. Recently, Sung and Dimitrov (2010) showed that for ASHGs checking whether a core stable or strict core stable partition exists is NP-hard in the strong sense. Their reduction relied on the asymmetry of the players' preferences.…”
Section: Core and Strict Corementioning
confidence: 99%
“…This fact does not imply that checking the existence of a core stable partition is NP-hard. Recently, Sung and Dimitrov (2010) showed that for ASHGs checking whether a core stable or strict core stable partition exists is NP-hard in the strong sense. Their reduction relied on the asymmetry of the players' preferences.…”
Section: Core and Strict Corementioning
confidence: 99%
“…More precisely, he shows that determining whether there is a Nash stable, an individually stable, and a core stable coalition structure is NP-complete. In [24], Sung and Dimitrov show that the same results hold for ASHG. Aziz et al investigate the computational complexity for many concepts including the above five solution concepts [4].…”
Section: Introductionmentioning
confidence: 64%
“…Fractional hedonic games are related to additively separable hedonic games [see, e.g., , Olsen, 2009, Sung and Dimitrov, 2010. In both fractional hedonic games and additively separable hedonic games, each player ascribes a cardinal value to every other player.…”
Section: Related Workmentioning
confidence: 99%